ANALISIS PENERAPAN SISTEM TANGGAP DARURAT KEBAKARAN DI PT X - Muthahhari Lubis, Zaki; Soemirat, Juli; Agustian Permadi, Didin (ENVIROSAN : Jurnal Teknik Lingkungan, 2020)
Wildfire is an uncontrolled fire that can occur because of the reaction of 3 elements, namely combustible material, heat source, and oxygen. This fire has the potential to occur in industries that have these three elements, the impact of which can result in losses for company assets, including facilities and workers. Therefore, fires are one of the most common types of emergencies in the industry. For industries that have this potential hazard, it is necessary to have a fire emergency response system to prepare technical things that must be done when the fire occurs. PT X is one of the industries in Indonesia engaged in electronics that has the potential for fire hazards in 4 work areas, namely the office area, electronic production, mechanics, and solar modules. Thus, it is necessary to evaluate the fire emergency response system in PT X's work environment which includes emergency response management, active protection facilities, and life-saving facilities. The existing conditions of each component are compared with several applicable standards, namely NFPA 10, 13, 14, 72, 101, Kepmen PU No. 11/2000, and Permen PU No. 26/2008. The results showed that the application of the fire emergency response system at PT X on the basis of applicable standards was 57.75%. This figure shows the level of reliability with a value of Less (K) because there are some components for which the application does not yet exist and for some existing components, it is not in accordance with applicable standards. Â  Keyword: Fire, Industry, emergency response system